2018
DOI: 10.1002/aenm.201702734
|View full text |Cite
|
Sign up to set email alerts
|

Metal–Organic Framework Templated Pd@PdO–Co3O4 Nanocubes as an Efficient Bifunctional Oxygen Electrocatalyst

Abstract: The development of high‐efficiency bifunctional electrocatalyst for oxygen reduction and evolution reactions (ORR/OER) is critical for rechargeable metal–air batteries, a typical electrochemical energy storage and conversion technology. This work reports a general approach for the synthesis of Pd@PdO–Co3O4 nanocubes using the zeolite‐type metal–organic framework (MOF) as a template. The as‐synthesized materials exhibit a high electrocatalytic activity toward OER and ORR, which is comparable to those of commerc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
59
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(59 citation statements)
references
References 41 publications
0
59
0
Order By: Relevance
“…The electrochemical active surface area (ECSA) plays a significant role in the OER catalytic ability, while the double‐layer capacitance ( C dl ) is proportional to the ECSA of catalysts. Therefore, C dl of HHTP@ZIF‐67 and ZIF‐67 were measured via cyclic voltammetry at different scan rates in the non‐faradaic region, in which no redox progress would occur. As presented in Figure S9 (Supporting Information), the C dl value of HHTP@ZIF‐67 is 56.43 mF cm −2 , nearly one time larger than that of pure ZIF‐67 (32.08 mF cm −2 ).…”
Section: Methodsmentioning
confidence: 99%
“…The electrochemical active surface area (ECSA) plays a significant role in the OER catalytic ability, while the double‐layer capacitance ( C dl ) is proportional to the ECSA of catalysts. Therefore, C dl of HHTP@ZIF‐67 and ZIF‐67 were measured via cyclic voltammetry at different scan rates in the non‐faradaic region, in which no redox progress would occur. As presented in Figure S9 (Supporting Information), the C dl value of HHTP@ZIF‐67 is 56.43 mF cm −2 , nearly one time larger than that of pure ZIF‐67 (32.08 mF cm −2 ).…”
Section: Methodsmentioning
confidence: 99%
“…[12][13][14] In electrocatalysis, MOFs were used as precursors and/or sacrificial templates to prepare various electrocatalysts including metal oxides, phosphides, and sulfides supported on porous carbon through pyrolysis under different conditions. [15][16][17][18] However, the pyrolysis process completely destroys the intriguing structural and compositional properties of the precursors, and results in limited active sites and hindered reactant transport. To take full advantage of the unique properties of MOFs, it is reasonable to directly use them as (pre)electrocatalysts.…”
Section: Introductionmentioning
confidence: 99%
“…. ARTICLES (Table S1) [27,33,[41][42][43][44][45][46][47][48][49][50][51][52][53][54][55]. The results indicated that the VO-rich Co 2 AlO 4 possessed a high OER kinetics.…”
Section: Methodsmentioning
confidence: 96%